My Private Spa - Braun, Markus Sebastian 1966- (Braun Publishing, 2019)
In no other room are we as much focused on ourselves than in the bathroom. Today, architects and interior designers pay great attention to create a special and unique ambience for this private retreat. Elements of historic and traditional bath cultures are incorporated and combined with contemporary design and lifestyle concepts using surprising material combinations, high-quality fittings and innovative technologies. The design possibilities have never been more varied: whether purist simplicity or extravagant opulence, playful and ornate spa landscapes or small and intimate guest bathrooms, this book serves as a creative source of inspiration as well as a useful planning aid.
Keywords: Design; Badezimmer; Innenarchitektur; Bad; Badgestaltung